Açık Sahada Emc Anteni Kalibrasyonlarının Gerçekleştirilmesi, Saha Doğrulaması Ve Ölçüm Belirsizliği - Coşkun, İlkcan (Fen Bilimleri Enstitüsü, 2015)
Üretilen her elektriksel, elektronik veya elektrik/elektronik kısmı bulunan cihazın başka cihazlara, ortama ya da insan sağlığına zararlı elektromanyetik girişim sinyalleri yayıp yaymadığı, ya da başka cihazlardan ya da ortamdan gelebilecek girişimlere karşı kendi özelliklerini ne kadar koruyabildiği EMC (Elektromanyetik Uyumluluk) testleri ile belirlenir. EMC testlerinin önemli elemanlarından biri ise EMC antenleridir. EMC antenlerinin özellik ve kalitesini belirleyen birçok parametre bulunmakla beraber, anten faktörü bu parametrelerin en önemlilerinden biridir. Antenlere ait anten faktörü değerleri EMC testlerinin doğruluğu, güvenilirliği ve kalitesi açısından son derece önemlidir. Anten faktörü değerlerinin güncelliği ise periyodik kalibrasyonlar ile sağlanır. EMC anteni kalibrasyonu aslında antenin anten faktörü ölçümünü ifade etmektedir. Bu noktada, ölçümün yetkin bir laboratuvar tarafından yapılıp sertifikalandırılması ve periyodik olarak kalibrasyon takibinin yapılması gerekmektedir. Anten faktörü olarak üretici değerlerinin kullanılması, uzun vadede hataları da beraberinde getirmektedir. Çünkü, geçen sürede antenler de kullanım veya başka sebeplerden değişim geçirmektedir. Bu noktada, güncel durumun ortaya konması önem arz etmektedir. Kalibrasyon ile güncel değerler elde edildiği gibi, kalibrasyonları periyodik olarak takip edilen bir antenin, uzun vadeli davranışı tespit edilerek bir nevi künyesi de oluşturulmaktadır. Bu çalışmada EMC antenlerinin Türk Standartları Enstitüsü bünyesinde bulunan Açık Saha Test Alanı’nda kalibrasyonlarının gerçekleştirilmesi hedeflenmiş, açık sahadaki bu kalibrasyonlara ait ölçüm belirsizliği hesabı yapılmaya çalışılmıştır. Öncelikle sahanın kalibrasyon yeterliliği tartışılmış ve ANSI C63.4-2014 standardına göre saha doğrulaması yapılarak kalibrasyon yeterliliği test edilmiştir. Sonuçlar, sahanın kalibrasyonlara uygun olduğunu göstermiş ve bu aşamadan sonra kalibrasyonlar üzerinde çalışılmaya başlanmıştır. ANSI C63.5-2006 standardına göre 30 MHz-1 GHz frekans bandında bikonik, log-periyodik ve dipol antenlerle kalibrasyonlar gerçekleştirilmiştir. Standartta yer alan “Standart Saha Metodu” kullanılmış ve bu metodun alt metotları olarak nitelendirilebilecek ve bu çalışmaya özel olarak 3 Anten ile Standart Saha Metodu, Bilinen Anten ile Standart Saha metodu ve Özdeş Antenler ile Standart Saha Metodu olarak adlandırılan yöntemler uygulanmış, sonuçlar karşılaştırılmıştır. Karşılaştırma sonuçları üzerinde sebep-sonuç ilişkisi kurularak öngörüler ortaya konulmuştur. Çalışmada, 3 Anten ile Standart Saha Metodu ve Bilinen Anten ile Standart Saha Metodu, bikonik ve log-periyodik antenler üzerinde karşılaştırıldığında sonuçların farklılıklar gösterdiği görülmüştür. Bu farklılıkların, Bilinen Anten ile Standart Saha Metodu’nda bilinen anten olarak kullanılan antenin son sertifikasından çalışma zamanına kadar olan dönemde anten faktörlerinin değişiminden kaynaklandığı düşünülmektedir. Bu durum, 3 Anten ile Standart Saha Metodu’nun daha doğru ve güvenilir sonuçlar verdiğini göstermiştir. Özdeş Antenler ile Standart Saha Metodu mevcut bulunan yarım-dalga dipol setlerle uygulandığında, elde edilen değerlerin bu antenlerin üretiminden uzun yıllar geçmesine rağmen, üretici değerleri ile oldukça uyumlu olduğu görülmüştür. Ölçüm belirsizliği çalışması bu çalışmanın önemli bir kısmını teşkil etmektedir. Kalibrasyonların açık sahada yapılıyor olması ve kontrol odasının iklimlendirme teşkilatının bulunmaması, çokça ölçüm belirsizliği bileşeni olmasına sebebiyet vermiş, çalışma içerisinde bu bileşenler incelenerek ölçüm belirsizliği hesaplanmıştır. Ölçüm belirsizliği bütçesi oluşturulmuş, baskın ve ihmal edilebilir parametreler ortaya konmaya çalışılmıştır. Ölçüm belirsizliği 3 anten ile Standart Saha Metodu için hesaplanmış, GUM ve EA-4/02 dökümanlarına uygun olarak hazırlanmıştır. Ölçüm belirsizliğinde en baskın etkenin saha ve sistem kaynaklı etkiler olduğu görülmüştür. Ölçümde kullanılan cihazların frekans özelliklerinin belirsizliğe katkısının ise çok düşük, hatta ihmal edilebilecek düzeyde olduğu tespit edilmiştir.

It is so important to determine the level of electromagnetic interferences (EMI) which an electric/electronic device produces or the level of the resistance of a device to the electromagnetic interferences, since electromagnetic interferences can be harmful to devices, ambients or people. This can be determined by electromagnetic compatibility (EMC) tests. EMC antennas are an important part of EMC Tests, especially for radiated emission and immunity tests. EMC Antennas have various parameters such as polarization, beamwidth, gain, Voltage-Standing-Wave-Ratio (VSWR), phase center, impedance, antenna factor etc. Antenna factor is one of the important parameters among these parameters.of EMC antennas, also. It is crucial to know antenna factors exactly and clearly to maintain EMC test quality, accuracy and reliability. At this point, the calibration of EMC antennas is critical. The antenna factor values of manufacturers are often inadequate. Using manufacturer antenna factor values may cause some errors in EMC tests, since some changes may occur for antenna between manufacturing time and using time. So, periodic calibrations of EMC antennas are critical to obtaining current antenna factor values. Actually, “the calibration of an antenna” means measuring the antenna factors of that antenna. In addition to obtaining current antenna factor values, the long-term behaviour of an antenna can be revealed by periodic calibrations. For calibration quality, calibration staff qualifications, calibration laboratory and its infrastructure are very substantial. In the introduction part of this thesis, some basic information about Open-Area Test Site (OATS), Turkish Standard Institute, EMC tests, metrology, calibration, the uncertainty of measurement, the importance of EMC antenna calibration and measurement units is available. Review of the literature and standards on the subject takes place in this part, also. In this study, it is aimed that EMC antenna calibrations to be performed in Open-Area Test Site of Turkish Standard Institute with measurement uncertainty calculations. Initially, it was important to determine the convenience of the site for calibrations. To determine this, ANSI C63.4-2014 standard was used. Normalized Site Attenuation (NSA) tests were performed over a volume of the site. Normalized Site Attenuation values are basically obtained by subtracting antenna factors of antennas from site attenuation values. After determining normalized site attenuation values by measurements and calculations, the theoretical normalized site attenuation values and measured normalized site attenuation values are compared. At the end of the tests, it was revealed that the site was convenient for the calibration of EMC antennas. It was so crucial, because a calibration in an inconvenient site is inaccurate. After NSA tests and determining the convenience of the site, antenna calibration studies were initiated. Antenna calibrations were performed for biconical, log-periodic and tuned dipoles and for a frequency band from 30 MHz to 1 GHz. ANSI C63.5-2006 standard was used for calibration studies. “Standard Site Method” of ANSI C63.5-2006 Standard is the main method in this study. The applied points which differ from the standard in the scope of this study are expressed in the related parts of this study. All site attenuation measurements were taken in the same measurement geometry (horizontal distance between antennas: 10 m, transmitting antenna height : 2 m, receiving antenna height : 1 m-4 m, horizontal polarization). To determine site attenuation values, discrete frequency method was used. Standard Site Method was implemented with its sub-methods. These sub-methods are specifically named in the scope of this study as “Standard Site Method with Three Antennas”, “Standard Site Method with Known Antenna”, “Standart Site Method with Identical Antennas”. These methods were compared and some comments were made on the results. In the study, the results of Standard Site Method with Three Antennas and Standard Site Method with Known Antenna were compared on both biconical and log-periodic antennas. The results showed some differences with each other. It is thought to have originated from the antenna factor changes of “the known antenna” between last calibration time and working time. This shows Standard Site Method with Three Antennas is more accurate and reliable than Standart Site Method with Known Antenna. When Standart Site Method with Identical Antennas was implemented with half-wave dipole sets, the results and the manufacturer values were so similar although it has been many years since the production. Air temperature and relative humidity in Open-Area Test Site (OATS) were measured and stored by digital temperature and humidity gauge during the calibration processes. In addition, air pressure and wind speed were measured by digital pressure gauge and anemometer. In the control room, temperature and relative humidity were measured and stored by analogue temperature and relative humidity gauge during the calibration process. The uncertainty of measurement study is an important part of this study. There are a lot of uncertainty parameters because of open area conditions and a control room without air conditioning system. These parameters were analyzed in detail and the measurement uncertainty was calculated for Standart Site Method with Three Antennas. The measurement uncertainty budget has been built. Overall calculations of measurement uncertainty were made in accordance with GUM and EA-4/02 documents. Warm-up times of all devices are taken into account. The calculations showed that the most dominant factor was site and system effects. Therefore, it can be said that site qualifications have significant effect on the calibration of antennas in open field. The other dominant factor of measurement uncertainty was spectrum analyzer amplitude based factors. The calculated uncertainty contribution of the frequency characteristics of the devices that were used in the measurements were very small comparing to other uncertainty components. So, it was determined that it can be neglected. Three site attenuation measurement uncertainty values were very close to each other. The components which have negligible effect on measurement uncertainty were explained in the study. The calibration certificates of the antennas which calibrated in this study are located in Annex-A. Also, the calibration certificates of some devices that were used in calibration processes are located in Annex-B.
Performing Emc Antenna Calibrations In Open Area, Site Validation And Measurement Uncertainty
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: elektromanyetik uyumluluk (emc); kalibrasyon; elektromanyetik ölçüm; saha zayıflaması; açık saha anten test alanı; ölçüm belirsizliği; Emc anteni; bikonik anten; log-periyodik anten; dipol anten; saha doğrulaması; electromagnetic compatibility (emc); calibration; electromagnetic measurement; site attenuation; open area antenna test site; measurement uncertainty; Emc antenna; biconical antenna; log-periodic antenna; dipole antenna; site validation